A novel seesaw-like piezoelectric energy harvester for low frequency vibration. (15th December 2022) - Yu, Han; Hou, Chengwei; Shan, Xiaobiao; Zhang, Xingxu; Song, Henan; Zhang, Xiaofan; Xie, Tao
Abstract: This paper presents a novel seesaw-like piezoelectric energy harvester which has rotating motions to enhance the harvesting performance at low frequency vibrations. Firstly, the designing of the harvester with the specific structure was accomplished, and then the finite element analysis was conducted to simulate its dynamic characteristics. Finally, the prototype of the harvester was fabricated whose power generating behaviors were experimentally investigated. The influence of key structural parameters on the energy harvesting performance was evaluated by a combination of simulation and experiment. The effect of the inertia difference on the energy harvester characteristics was studied innovatively. The results indicated that the energy harvester reached the second-order resonance at a low frequency due to the adoption of the rotating shaft. And the piezoelectric material was involved in a significant strain due to the inertia difference between both ends of the beam. The efficiency of the harvester is relevant to the system moment of inertia and the excitation acceleration. The second-order resonant frequency of the harvester is as low as 19.18 Hz. When the excitation acceleration is 2.94 m/s 2, the maximum output voltage and power of the harvester are 49.15 V and 4.03 mW respectively, which demonstrates the superior harvesting performance of the structure. This work can provide a novel method for designing efficient ambient energy harvesters supplying for low-power electronic devices. Highlights: A new seesaw-like piezoelectric energy harvester with a rotating motion is designed. The harvesting performance is investigated by simulation combined with experiments. The second-order natural frequency of the harvester is as low as 19.18 Hz. The enhanced performance in the low-frequency environmental vibration is verified.